2022
DOI: 10.1073/pnas.2201645119
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes maintain central nervous system homeostasis following helminth-induced inflammation

Abstract: Neuroimmune interactions are crucial for regulating immunity and inflammation. Recent studies have revealed that the central nervous system (CNS) senses peripheral inflammation and responds by releasing molecules that limit immune cell activation, thereby promoting tolerance and tissue integrity. However, the extent to which this is a bidirectional process, and whether peripheral immune cells also promote tolerance mechanisms in the CNS remains poorly defined. Here we report that helminth-induced type 2 inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…By integrating estimated cell-type compositions, our analysis revealed that the post-infusion DEG signature was primarily driven by changes in monocyte-specific gene expression. Monocytes, as immune cells involved in inflammatory responses, play crucial roles in shaping the immune milieu within the central nervous system (Peng, et al, 2022; Arteaga-Henríquez, et al, 2022; Xie, et al, 2017). The upregulation of genes associated with immune and inflammatory processes observed in our study aligns with previous evidence highlighting the involvement of the immune system in the pathophysiology of neurodevelopmental disorders, including ASD (Arteaga-Henríquez, et al, 2022l; Molloy, et al, 2005; Gupta, et al, 1998; Dantzer, et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…By integrating estimated cell-type compositions, our analysis revealed that the post-infusion DEG signature was primarily driven by changes in monocyte-specific gene expression. Monocytes, as immune cells involved in inflammatory responses, play crucial roles in shaping the immune milieu within the central nervous system (Peng, et al, 2022; Arteaga-Henríquez, et al, 2022; Xie, et al, 2017). The upregulation of genes associated with immune and inflammatory processes observed in our study aligns with previous evidence highlighting the involvement of the immune system in the pathophysiology of neurodevelopmental disorders, including ASD (Arteaga-Henríquez, et al, 2022l; Molloy, et al, 2005; Gupta, et al, 1998; Dantzer, et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotection also occurs during the intestinal response to Trichinella spiralis , where monocytes recruited to the brain express M2 markers and inhibit excessive microglial cell activation. This tolerance mechanism persists for months and also protects against lipopolysaccharide-induced neuroinflammation ( Peng et al, 2022 ).…”
Section: Aftermath: Repair and Return To Homeostasismentioning
confidence: 99%